Kernel regression estimation for LTRC and associated data - Bey, Siham; Guessoum, Zohra; Tatachak, Abdelkader (Communications in statistics. Theory and methods, 2023)
This paper focuses on nonparametric regression modeling of time-series and incomplete observations. In this sense, the observations are subject to both left truncation and right censoring (LTRC) and satisfy an association dependency. Using the well-known kernel estimation method, we establish the strong uniform consistency with a rate of the kernel estimator proposed in this paper. Simulation studies are conducted to assess the impact of both incompleteness and association dependency on the estimation.